Mitophagy alterations in Alzheimer's disease are associated with granulovacuolar degeneration and early tau pathology. Issue 3 (8th October 2020) - Hou, Xu; Watzlawik, Jens O.; Cook, Casey; Liu, Chia‐Chen; Kang, Silvia S.; Lin, Wen‐Lang; DeTure, Michael; Heckman, Michael G.; Diehl, Nancy N.; Al‐Shaikh, Fadi S. Hanna; Walton, Ronald L.; Ross, Owen A.; et al.
Abstract: Introduction: The cytoprotective PTEN‐induced kinase 1 (PINK1)‐parkin RBR E3 ubiquitin protein ligase (PRKN) pathway selectively labels damaged mitochondria with phosphorylated ubiquitin (pS65‐Ub) for their autophagic removal (mitophagy). Because dysfunctions of mitochondria and degradation pathways are early features of Alzheimer's disease (AD), mitophagy impairments may contribute to the pathogenesis. Methods: Morphology, levels, and distribution of the mitophagy tag pS65‐Ub were evaluated by biochemical analyses combined with tissue and single cell imaging in AD autopsy brain and in transgenic mouse models. Results: Analyses revealed significant increases of pS65‐Ub levels in AD brain, which strongly correlated with granulovacuolar degeneration (GVD) and early phospho‐tau deposits, but were independent of amyloid beta pathology. Single cell analyses revealed predominant co‐localization of pS65‐Ub with mitochondria, GVD bodies, and/or lysosomes depending on the brain region analyzed. Discussion: Our study highlights mitophagy alterations in AD that are associated with early tau pathology, and suggests that distinct mitochondrial, autophagic, and/or lysosomal failure may contribute to the selective vulnerability in disease.